Life cycle assessment of raw and fried tette chips production - Ulya, Millatul; Mu?tamar, M. Fuad Fauzul; Firmansyah, R. Arief (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2020)
Madura has typical cassava-based food products including cassava chips, raw tette chips and fried tette chips produced by Small and Medium-sized Enterprises (SMEs). The production process of the three products varies and produces different environmental impacts. This study aims to evaluate and compare environmental impact assessments in the production of raw tette chips and fried tette chips using Life Cycle Assessment (LCA) approach. This study evaluates the product life cycle from the procurement of raw materials until the product is consumed. The results showed that fried tette chips had a lower environmental impact than raw tette chips per 500 gram basis. Climate change, photochemical oxidation and eutrophication are environmental impacts identified in this study. The results of this study are expected to get a comprehensive environmental footprint of the product system with respect to sustainable production and consumption.